Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska, Grzegorz Janocha
Wydawnictwo:Nowa Era
Rok wydania:2016
Podaj odpowiednie założenia i wykonaj działanie 4.67 gwiazdek na podstawie 9 opinii

Podaj odpowiednie założenia i wykonaj działanie

1Zadanie
2Zadanie
3Zadanie
4Zadanie
5Zadanie
6Zadanie
1Zadanie
2Zadanie

`a)` 

`{(4xne0), (x^2ne0):}\ \ \ =>\ \ \ {(xne0), (xne0):}\ \ \ =>\ \ \ D=RR\\{0}` 

 

`1/(4x)+2/(x^2)=(x^2)/(4x*x^2)+(2*4x)/(x^2*4x)=x^2/(4x^3)+(8x)/(4x^3)=(x^2+8x)/(4x^3)` 

 

 

 

`b)` 

`{(2x^2ne0), (5xne0):}\ \ \ =>\ \ \ {(xne0), (xne0):}\ \ \ =>\ \ \ D=RR\\{0}` 

 

`3/(2x^2)-1/(5x)=(3*5x)/(2x^2*5x)-(2x^2)/(2x^2*5x)=(15x)/(10x^3)-(2x^2)/(10x^3)=(15x-2x^2)/(10x^3)=(15-2x)/(10x^2)` 

 

 

 

`c)` 

`2xne0\ \ \ =>\ \ \ x ne0\ \ \ =>\ \ \ D=RR\\{0}` 

 

`(4x)/3-1/(2x)=(4x*2x)/(3*2x)-3/(3*2x)=(8x^2)/(6x)-3/(6x)=(8x^2-3)/(6x)` 

 

 

 

`d)`    

`{(3x^2ne0), (2x^3ne0):}\ \ \ \ =>\ \ \ {(xne0), (xne0):}\ \ \ =>\ \ \ D=RR\\{0}` 

 

`2/(3x^2)+3/(2x^3)=(2*2x)/(3x^2*2x)+(3*3)/(2x^3*3)=(4x)/(6x^3)+9/(6x^3)=(4x+9)/(6x^3)`